Use of the Universal Soil-Loss Equation to determine water erosion with the semi-circular bund water-harvesting technique in the Syrian Steppe - Al Mahmoud, Hamdan; Al Issam, Khouri; Awadis, Arslan (International Journal of Environment, 2014)
This research was conducted through the rain season 2009 -2010, in Mehasseh Research Center at (Al Qaryatein), The area is characterized by a hot and dry climate in summer and cold in winter with an annual average rainfall of 114 mm. Three slopes (8%, 6%, 4%) were used in semicircular bunds water -harvesting techniques with bunds parallel to the contours lines at flow distance of 18, 12 and 6 m. The bunds were planted with Atriplex Halimus seedlings. Graded metal rulers were planted inside the bunds to determine soil loss and sedimentation associated with the surface runoff, and metallic tanks were placed at the end of the flow paths to determine agricultural soil loss from water runoff. A rain intensity gauge was placed near the experiment site to determine the rainfall intensity that produced runoff. The treatments were done in three replications. The amount of soil erosion (in tons per hectare per year) increased with increasing of the slope, the highest recorded value was 38.66 at slope of 8% and the lowest 0.05 at 4% slope. The amount of soil erosion also increased with increasing of water run distance, which was 38.66 T.ha-1.yr-1 at 18 m and 0.05 T.ha-1.yr-1 at 6 m . Bunds with different diameter of water harvesting reduced soil erosion by about 65% at slope of 8%, 55% at 6%, and 46% at 4%. The input parameters of Universal soil-loss equation were found to be suitable for determining soil erosion in this arid and semi-arid region. DOI: http://dx.doi.org/10.3126/ije.v3i2.10499 International Journal of the Environment Vol.3(2) 2014: 1-11